Simulasi Numerik Reaksi Fusi Nuklir dengan menggunakan Metode Wong - Muhammad Zamrun Firihu; Viska Inda Variani; J Justina (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2016)
The numerical simulation for calculating the cross section of fusion reaction is done by using Wong formula. We especially calculated the cross section for the fusion reaction of light systems, i.e. 12C+12C, 16O+12C and 16O+16O reactions. We compared the obtained cross section with experimental data. In order to check the accuracy of the calculations, the chi-square analisys is then permormed. We found that the simulation results of the fusion cross section obtained using Wong Formula well explain the experimetal data of the fusion cross section for the 12C+12C, 16O+12C and 16O+16O reactions. This finding indicates that the Wong formula can be used for studing the fusion reaction of light systems.